IINFLUENCE OF FREEZING AND PROLONGED STORAGE OF EXPRESSED BREAST MILK ON ITS NUTRITIVE, BIOLOGICAL VALUES AND MICROBIOLOGICAL SAFETY - O. L. Lukoyanova; T. E. Borovik; I. A. Belyayeva; N. A. Mayanskiy; L. K. Katosova; A. N. Kalakutskaya; I. V. Zubkova; O. S. Mel'nichuk ("Paediatrician" Publishers LLC, 2011)
Evaluation of prolonged storage of breast milk safety for nutrition of newborns remains actual problem of modern nutritiology. Objectives: to evaluate an influence of freezing and prolonged storage of expressed breast milk on its nutritive, biological values and microbiological safety. Methods: samples of expressed breast milk (native samples and after 1 and 3 months of storage in containers Philips AVENT in t -18°С) were analyzed; levels of secretory IgA, lysozyme, transforming growth factor (TGF) β1, potassium, calcium, magnesium, pH, buffer capacity and bacterial cells were detected. Results: there is no statistically significant influence of low temperature and prolonged storage of expressed breast milk on levels of secretory IgA, lysozyme, TGF β1 and bacterial cells. Potassium and calcium levels significantly decreased (on about 10% and 20% accordingly), pH increased, and buffer capacity of milk lowered after freezing during 3 months. Conclusion: children's feeding with native and expressed breast milk defrosted after 3 months of storage is equal in nutritive and biological values and microbiological safety.